A sodium background conductance controls the spiking pattern of mouse adrenal chromaffin cells in situ - Milman, Alexandre (John Wiley and Sons Inc., 2021)

(untitled) (J Physiol)
KEY POINTS: Mouse chromaffin cells in acute adrenal slices exhibit two distinct spiking patterns, a repetitive mode and a bursting mode. A sodium background conductance operates at rest as demonstrated by the membrane hyperpolarization evoked by a low Na(+)‐containing extracellular saline. This sodium background current is insensitive to TTX, is not blocked by Cs(+) ions and displays a linear I‐V relationship at potentials close to chromaffin cell resting potential. Its properties are reminiscent of those of the sodium leak channel NALCN. In the adrenal gland, Nalcn mRNA is selectively expressed in chromaffin cells. The study fosters our understanding of how the spiking pattern of chromaffin cells is regulated and adds a sodium background conductance to the list of players involved in the stimulus‐secretion coupling of the adrenomedullary tissue. ABSTRACT: Chromaffin cells (CCs) are the master neuroendocrine units for the secretory function of the adrenal medulla and a finely‐tuned regulation of their electrical activity is required for appropriate catecholamine secretion in response to the organismal demand. Here, we aim at deciphering how the spiking pattern of mouse CCs is regulated by the ion conductances operating near the resting membrane potential (RMP). At RMP, mouse CCs display a composite firing pattern, alternating between active periods composed of action potentials spiking with a regular or a bursting mode, and silent periods. RMP is sensitive to changes in extracellular sodium concentration, and a low Na(+)‐containing saline hyperpolarizes the membrane, regardless of the discharge pattern. This RMP drive reflects the contribution of a depolarizing conductance, which is (i) not blocked by tetrodotoxin or caesium, (ii) displays a linear I‐V relationship between −110 and −40 mV, and (iii) is carried by cations with a conductance sequence g (Na) > g (K) > g (Cs). These biophysical attributes, together with the expression of the sodium‐leak channel Nalcn transcript in CCs, state credible the contribution of NALCN. This inaugural report opens new research routes in the field of CC stimulus‐secretion coupling, and extends the inventory of tissues in which NALCN is expressed to neuroendocrine glands.